Kinetic analysis of the upper limbs in baseball tee-batting under low hitting point height condition - Ae, K.; Koike, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Hitting low height balls is more difficult for baseball batters in comparison to hitting high and middle height balls. The purpose of this study was to investigate the kinetic features of the individual upper limb joints among different skill level players in baseball tee-batting under the low hitting point height condition. Twenty-three collegiate baseball players were instructed to hit three kinds of hitting point height balls. Kinematic and kinetic analyses were implemented together with a motion capture system and an instrumented bat. The findings indicate that highly skilled batters exert great extension torque of the barrel-side (top hand) shoulder joint in the first half of the forward swing period in order to hit low point height balls. It is speculated that the large initial flexion angle of the barrel-side shoulder joint can help to increase the torque and angular velocity of the shoulder joint.